METHODOLOGICAL FOUNDATIONS FOR DEVELOPING SPEECH BREATHING BASED ON SPEECH THERAPY RHYTHMICS - Abdullayeva Karomat Islom qizi (THE HARMONY OF TRADITIONAL KNOWLEDGE AND MODERN INNOVATIONS, 2025)
Abstract: This article explores the methodological foundations for developing speech breathing in children through speech therapy rhythmics. The study examines how rhythmic exercises, including breathing patterns, vocalization, and coordinated movements, can improve respiratory control, enhance speech fluency, and support overall communicative competence. The research emphasizes the importance of integrating rhythm-based exercises into speech therapy sessions to strengthen respiratory coordination, facilitate clear articulation, and increase motivation during learning activities. Results highlight that speech therapy rhythmics provide a structured and engaging approach to developing proper speech breathing, contributing to both speech development and emotional regulation in children.